MEHNAT SAMARADORLIGI – TARAQQIYOTIMIZ OMILIDIR - Anvarova Lobarxon Sherzod qizi (International Scientific and Current Research Conferences, 2023)
In the article, the author thinks about increasing labor efficiency fnd labor productivity. According to him, the concept of practical labor efficiency allows to express the productivity of labor in an enterprice or indutry. In a society where the labor process is organized taking these factors into account,labor efficiency in enterprises fnd organizations increases gradually. Also, the article emphasizes that labor productivity occurs in economic, political and spiritual forms.